1975
DOI: 10.1161/01.res.37.5.580
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-accumulating properties of subcellular fractions of bovine vascular smooth muscle.

Abstract: This study examined the calcium transport properties of two subcellular fractions of bovine aorta obtained by differential centrifugation. The vesicular fraction had a high-affinity (K m = 1.05 x 10~6M) calcium transport mechanism which could be potentiated by using the calcium-precipitating anion, oxalate. The mitochondriaenriched fraction's calcium transport system had a lower affinity for calcium than did that of the vesicular fraction. The calcium capacity of the vesicular fraction was determined by compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

1977
1977
1991
1991

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…The addition of the inorganic anions, oxalate and phosphate, which are known to stimulate calcium sequestration in both cardiac and skeletal muscle by precipitating calcium within the vesicles [21], had no effect on the aortic microsomes. The lack of oxalate stimulation differs from the results obtained with aortic microsomes by others [11,12,14,15] who showed significant stimulation by these agents. Basically the same isolation technique is used here as described by F itzpatrick el al.…”
Section: MMcontrasting
confidence: 99%
See 2 more Smart Citations
“…The addition of the inorganic anions, oxalate and phosphate, which are known to stimulate calcium sequestration in both cardiac and skeletal muscle by precipitating calcium within the vesicles [21], had no effect on the aortic microsomes. The lack of oxalate stimulation differs from the results obtained with aortic microsomes by others [11,12,14,15] who showed significant stimulation by these agents. Basically the same isolation technique is used here as described by F itzpatrick el al.…”
Section: MMcontrasting
confidence: 99%
“…[15]. D 'A uriac et al [8], F ord and H ess [12] and H ess and F ord [14] used imidazole buffer. as indicated in the absence of any A number of other compounds reported to affect calcium binding or release in cardiac relaxing system did not affect the aortic microsomes.…”
Section: MMmentioning
confidence: 99%
See 1 more Smart Citation
“…In initial microsomal studies [Katz and Repke, 1967;Harigaya and Schwartz, 1969;Ford and Hess, 1975], Ca++ incorporation in the presence of both ATP and oxalate was designated as Ca++ 'uptake'. Ca++ incorpora tion in the presence of ATP but not of oxalate was designated Ca++ 'binding'.…”
Section: Discussionmentioning
confidence: 99%
“…18 -19 '"-" From studies on microsomal fraction of smooth muscle, Ford and Hess 28 concluded that the microsomes sequestered sufficient Ca 2+ and that this fraction has the capability to be both sink and source for the activator Ca 2+ in excitation-contraction coupling. Observations made in this laboratory" and by others 8 "' demonstrate that incubation of smooth muscle microsomal fraction with cAMP-dependent protein kinase enhances energy-dependent Ca l+ sequestration, which suggests a modulatory role for cAMP-dependent protein kinase in Ca 2+ transport in vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 99%